2001
DOI: 10.1002/1098-2795(200103)58:3<245::aid-mrd1>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of full-length cDNA encoding delta-9 desaturase through PCR strategies and its genomic organization and expression in grass carp (Ctenopharyngodon idella)

Abstract: Desaturases are enzymes that catalyze double bond formation in fatty acids, which is a critical step in the synthesis of unsaturated fatty acids in organisms. Desaturase cDNA has been cloned from various species. Here we report the cloning of a full‐length cDNA of Δ9‐desaturase from grass carp (Ctenopharyngodon idella), using a combination of PCR techniques: reverse transcription–polymerase chain reaction (RT‐PCR) and rapid amplification of cDNA ends (RACE). The resolved cDNA encompasses 2420 bp, containing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 49 publications
3
22
0
Order By: Relevance
“…SCD-1 is mainly expressed in adipose tissues and liver (Ntambi et al, 1988), SCD-2 is principally expressed in brain (Kaestner et al, 1989), SCD-3 is skinspecifically expressed (Zheng et al, 2001), whereas SCD-4 is exclusively expressed in the heart . Similarly, SCD was only expressed in the liver and brain of the grass carp (Chang et al, 2001), and exclusively in the liver of the common carp (Polley et al, 2003). In contrast, SCD genes are ubiquitously expressed in human (Zhang et al, 1999), goat (Yahyaoui et al, 2002), sheep (Ward et al, 1998), zebrafish (Hsieh et al, 2003) and milkfish (Hsieh et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCD-1 is mainly expressed in adipose tissues and liver (Ntambi et al, 1988), SCD-2 is principally expressed in brain (Kaestner et al, 1989), SCD-3 is skinspecifically expressed (Zheng et al, 2001), whereas SCD-4 is exclusively expressed in the heart . Similarly, SCD was only expressed in the liver and brain of the grass carp (Chang et al, 2001), and exclusively in the liver of the common carp (Polley et al, 2003). In contrast, SCD genes are ubiquitously expressed in human (Zhang et al, 1999), goat (Yahyaoui et al, 2002), sheep (Ward et al, 1998), zebrafish (Hsieh et al, 2003) and milkfish (Hsieh et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…SCD genes have been so far characterized in human (Zhang et al, 1999), mouse (Ntambi et al, 1988;Kaestner et al, 1989), rat (Mihara, 1990), goat (Yahyaoui et al, 2002;Bernard et al, 2001), sheep (Ward et al, 1998), housefly (Eigenheer et al, 2002), zebrafish (Hsieh et al, 2003), milkfish (Hsieh et al, 2001), grass carp (Chang et al, 2001), and common carp (Polley et al, 2003). Prior to our project, a 1003-bp-long partial porcine SCD mRNA sequence was deposited in the database (GenBank accession no.…”
Section: Discussionmentioning
confidence: 99%
“…SCD1 is mainly expressed in the liver, whereas SCD2 and SCD5 are mainly expressed in the brain, and SCD3 and SCD4 are tissue-specific proteins expressed in the skin and heart, respectively (Hodson and Fielding, 2013;Lengi and Corl, 2007;Miyazaki et al, 2003;Ntambi and Miyazaki, 2003;). In fish, only two SCD isoforms, SCD1 and SCD2 were found in grass carp (Ctenopharyngodon idella), and were highly expressed in the liver but low in the brain (Chang et al, 2001;Polley et al, 2003;Evans et al, 2008). In tilapia, SCD1 was only expressed in the liver (Hsieh et al, 2004), while in milkfish and zebrafish, SCD1 was found in various tissues (Hsieh et al, , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, besides the soluble D9-ACP desaturases, the other two classes of membrane-bound D9-desaturases in different species could be regarded as alternative desaturase resource for more efficient production of PUFAs. However, although most research has been done on the D9 acyl-lipid desaturase isolated from cyanobacteria [31][32][33][34], the number of prokaryotic D9-desaturase enzymes that have been investigated in detail is much smaller than those from fungi [35,36], higher plants [10,37], fish [38] and mammals [39] so far. In the present study, a novel gene that encodes a membrane-bound D9-fatty acid desaturase from P. urativorans has been cloned and, to our knowledge, for the first time, successfully expressed in E. coli.…”
Section: Discussionmentioning
confidence: 99%